2011
DOI: 10.1007/s10008-011-1569-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical characterization of aPEO-based polymer electrolytes

Abstract: In this paper, the preparation and purification of an amorphous polymer network, poly[oxymethylene-oligo (oxyethylene)], designated as aPEO, are described. The flexible CH 2 CH 2 O segments in this host polymer combine appropriate mechanical properties, over a critical temperature range from −20 to 60°C, with labile salt-host interactions. The intensity of these interactions is sufficient to permit solubilisation of the guest salt in the host polymer while permitting adequate mobility of ionic guest species. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…3(c), inset] consists of two resistors: R s corresponding to the ohmic resistance at high frequency and R ct corresponds to the charge transfer resistance of the electro-des, a Warburg element (W) which accounts for the diffusion reactance at low frequencies, and a constant phase element (CPE) corresponding to the double layer charging (C dl ) at the porous electrode/electrolyte interfaces; CPE is used instead of an ideal capacitor because of the depressed shape of the Nyquist semicircle. 21 Results suggest an R s value of approximately 242 X, which includes the electrolyte resistance as well as the ohmic resistance of the battery cell and an R ct of approximately 327 X. The relatively large value of R ct is presumed to be an indication of poor connection between the electrodes and electrolyte layer.…”
mentioning
confidence: 96%
“…3(c), inset] consists of two resistors: R s corresponding to the ohmic resistance at high frequency and R ct corresponds to the charge transfer resistance of the electro-des, a Warburg element (W) which accounts for the diffusion reactance at low frequencies, and a constant phase element (CPE) corresponding to the double layer charging (C dl ) at the porous electrode/electrolyte interfaces; CPE is used instead of an ideal capacitor because of the depressed shape of the Nyquist semicircle. 21 Results suggest an R s value of approximately 242 X, which includes the electrolyte resistance as well as the ohmic resistance of the battery cell and an R ct of approximately 327 X. The relatively large value of R ct is presumed to be an indication of poor connection between the electrodes and electrolyte layer.…”
mentioning
confidence: 96%
“…Due to the high crystallinity of PEO, PEO‐based SPEs have a low ionic conductivity (10 −8 –10 −7 S cm −1 ) at room temperature, which does not meet the requirement for ionic conductivity (>10 −4 S cm −1 at room temperature) of electrolytes with promising applications. [ 33,36,37 ] Many strategies, such as adding inorganic nanoparticles, [ 38–40 ] blending, [ 41 ] copolymerization, [ 42 ] and crosslinking [ 43–45 ] have been adopted to effectively suppress the crystallization of PEO and improve the ionic conductivity of PEO‐based SPEs. Coat et al [ 46 ] reported the synthesis of poly(diethylene oxide‐alt‐oxymethylene) (P(2EO‐MO)) as a polymer matrix for SPE, which has higher T g than that of PEO in the electrolyte.…”
Section: Figurementioning
confidence: 99%